2012
DOI: 10.4491/eer.2012.17.2.103
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Atmospheric Volatile Organic Compound Characteristics in Specific Areas in Korea Using Long-Term Monitoring Data

Abstract: This study was performed mainly to examine whether a city with a metal industrial presence presents different characteristics in ambient volatile organic compound (VOC) concentrations compared to residential (RES) and commercial/residential combined (CRC) areas of another city by using long-term monitoring data (from January 2006 to February 2009). For most target VOCs, ambient concentrations in the metal-industrialized city were lower than for the RES and CRC areas. Aromatic compounds were the predominant VOC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 36 publications
0
2
0
Order By: Relevance
“…This assertion is supported by the finding that the indoor concentrations of those halogenated VOCs were similar to the outdoor concentrations, suggesting that the indoor concentrations resulted from penetration of outdoor compounds. Outdoor halogenated VOCs primarily result from industrial processes such as petroleum refinery, storage and transportation, water and waste water treatment plants, municipal solid waste storage, and commercial which are used as solvents and degreasing agents [24][25][26][27][28][29]. In particular, chloroform is generated during the water-disinfection processes and emitted to the ambient air from drinking-or waste-water treatment plants [25].…”
Section: Vocs In Newly-built Residential Buildingsmentioning
confidence: 99%
“…This assertion is supported by the finding that the indoor concentrations of those halogenated VOCs were similar to the outdoor concentrations, suggesting that the indoor concentrations resulted from penetration of outdoor compounds. Outdoor halogenated VOCs primarily result from industrial processes such as petroleum refinery, storage and transportation, water and waste water treatment plants, municipal solid waste storage, and commercial which are used as solvents and degreasing agents [24][25][26][27][28][29]. In particular, chloroform is generated during the water-disinfection processes and emitted to the ambient air from drinking-or waste-water treatment plants [25].…”
Section: Vocs In Newly-built Residential Buildingsmentioning
confidence: 99%
“…They also reported that phosphorus removal was not high enough in this method. Jo et al[9] evaluated the atmospheric volatile organic compound characteristics in Pohang, Korea, where metal industry is strong. Kwon and Jeon [10] contributed short communications where they reported desorption characteristics for previously adsorbed indium ions on phosphorylated sawdust by various chemical reagents such as HCl, HNO 3 , NaCl, ethylenediaminetetraacetic acid, and nitrilotriacetic acid.…”
mentioning
confidence: 99%